Nutrients Status of Kemaman River Basin in Southern South China Sea (Malaysia) - Suratman, S.; Y. Hee, Y.; Mohd Tahir, N. (Asian Journal of Chemistry, 2014)
Preliminary study of phosphorus and nitrogen-based nutrients was conducted at the Kemaman River basin, Terengganu, Malaysia. Surface water samples were taken monthly from July-November 2009. In general, higher concentrations of nutrients were recorded at the station near to agricultural activities. The study also showed that the nutrients concentrations were lower compared with other selected study areas. According to the National Water Quality Standards (NWQS) classification for Malaysia, the concentrations of orthophosphate, nitrite and nitrate were in Class I water quality indicating a natural level. No comparison based on National Water Quality Standards could be made for other parameters as they are still not listed in this classification.